Interview with Professor Dr. Rajesh Nath Gongal - Subedi, Madhusudan (Journal of Patan Academy of Health Sciences, 2025)
Professor Dr. Rajesh Nath Gongal is an academic and healthcare leader whose career blends surgical expertise with visionary institutional management. As a Professor of Surgery at the Patan Academy of Health Sciences (PAHS), Dr. Gongal has played a pivotal role in shaping medical education in Nepal. He is deeply committed to developing innovative curricula that produce socially responsible health care professionals. His academic contributions extend to research, including studies on empathy development among medical students and palliative care awareness, reflecting his commitment to both clinical excellence and humanistic medicine. Dr. Gongal has held several key managerial positions: he served as Medical Director of Patan Hospital, later became founding Dean, Rector and Vice-Chancellor of the Academy. He is the Founding President of Hospice Nepal, the country’s first palliative care center, and the Founding President of Nepal Ambulance Service, which introduced Emergency Medical Technician (EMT)-based emergency response through a three-digit number system. By initiating programs like Primary Trauma Care (PTC) training in Nepal, he has strengthened emergency medical preparedness across the nation. His academic leadership and managerial innovations have profoundly advanced Nepal’s medical education, healthcare delivery, and emergency response systems. The Journal of Patan Academy of Health Sciences extends its sincere gratitude to Professor Dr. Gongal for his generous and thoughtful engagement in answering the written questions prepared for this interview.